2012
DOI: 10.1111/j.1524-475x.2012.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of randomized clinical trials in wound care: Design and conduct

Abstract: The care for chronic and acute wounds is a substantial problem around the world. This has led to a plethora of products to accelerate healing. Unfortunately, the quality of studies evaluating the efficacy of such wound care products is frequently low. Randomized clinical trials are universally acknowledged as the study design of choice for comparing treatment effects, as they eliminate several sources of bias. We propose a framework for the design and conduct of future randomized clinical trials that will offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…Genome-wide techniques produce enormous amounts of data, and for proper analysis a bona fide professional is needed. 14,15 There is no standard clinical model available for chronic, nonhealing wounds, but the problem may be approached, to some extent, by studying normal wound healing. Split-thickness skin grafting is a standard procedure in many defects demanding skin cover; 0.01-inch-or 0.25-mm-thick grafts can be harvested in a very standardized way with a mechanical air-driven device (dermatome).…”
Section: Problems In Clinical Wound-healing Researchmentioning
confidence: 99%
“…Genome-wide techniques produce enormous amounts of data, and for proper analysis a bona fide professional is needed. 14,15 There is no standard clinical model available for chronic, nonhealing wounds, but the problem may be approached, to some extent, by studying normal wound healing. Split-thickness skin grafting is a standard procedure in many defects demanding skin cover; 0.01-inch-or 0.25-mm-thick grafts can be harvested in a very standardized way with a mechanical air-driven device (dermatome).…”
Section: Problems In Clinical Wound-healing Researchmentioning
confidence: 99%
“…[2][3][4][5][6] Nevertheless, the number of scientific publications in wound care shows a 30-fold increase over the last five decades.…”
mentioning
confidence: 99%
“…3,5,8 Unfortunately, upgrading the quality of a study design does not automatically improve the quality of reporting in wound care publications. 4,9-11 First, positive study results tend to be published more often than indifferent or negative study results, known as publication bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of wound care, high-quality evidence is lacking for many of the interventions commonly utilized. 39 Even in venous ulcers, a subset of wounds with good-quality evidence and multiple CPGs, healing rates remain low. In an analysis of real-world venous ulcer care in four settings, Jones found that only some of the evidence-based practice recommendations lead to superior outcome.…”
mentioning
confidence: 99%